VP163 Patient Involvement In The Development Of Multi-Criteria Decision Tool. (2017) - Gagnon, Marie-Pierre; L'Espérance, Sylvain; Lindsay, Carmen; Rhainds, Marc; Coulombe, Martin; Rousseau, François
Abstract : INTRODUCTION: Healthcare organizations should assess the relevance of both existing and new practices. Involving patients in decisions regarding which health technologies and interventions should be prioritized could favor a better fit between strategic choices and patients needs. METHODS: Following a systematic review of existing multi-criteria decision support tools and a consultation with hospital clinicians and managers, a set of potentially relevant criteria was identified. A three-round modified Delphi study was then conducted among four groups (hospital managers, heads of department, clinicians, and patient representatives) in order to reach consensus on criteria that should be considered in the tool. RESULTS: In total, seventy-four participants completed the third round of the Delphi study. Consensus was obtained on twelve criteria. There were some significant differences between groups in priority scores given to criteria. Patient representatives differed significantly from other groups on two criteria. Their ranking of the accessibility criteria was higher, and their ranking of the organizational aspect criteria was lower than for the other groups. CONCLUSIONS: Patient representatives can be involved in the development of a multi-criteria decision support tool to identify, evaluate and prioritize high value-added health technologies and interventions in order to enhancing clinical appropriateness The fact that accessibility aspects were more important for patient representatives calls for specific attention to these criteria when prioritizing health technologies or interventions. Furthermore, we need to ensure that the decisions made regarding the relevance of these technologies and interventions also reflect patients' preferences.